Improving fourth-grade students’ reading numerical notation using melodica through a directed learning method in elementary school - Uliy Elma Fadila; Sularso Sularso (Universitas Ahmad Dahlan, 2023)
This research is motivated by the less-than-optimal use of learning media and learning methods used by teachers in the learning process of music, especially the material of numerical notation in grade IV students of SD Muhammadiyah Noyokerten. This study aims to explain the steps in an effort to improve the ability to read numerical notation using a melodica through direct learning methods and determine the improvement in the ability to read numerical notation through direct learning methods using a melodica. The method used in this research is classroom action research. The subjects in this study were fourth-grade students of SD Muhammadiyah Noyokerten, totaling 18 students. The results showed an increase in students' ability to read numerical notation as evidenced by an increase in test scores by 51.9% and the results of observations of students' ability to read numerical notation using melodica musical instruments through direct learning methods in cycle I of 78.69% in the good category and cycle II of 95.5% in the very good category which increased by 16.81%. The contribution of this research is that the application of the direct learning method is able to improve students' ability to read numerical notation, and students can easily recognize numerical notation through demonstration and guidance from the teacher directly.